Гідрогеологічні умови Мелітопольської ділянки Мелітопольського міського водозабору - Даценко, Людмила Миколаївна; Даценко, Людмила Николаевна; Datsenko, Liudmyla; Сухаренко, Олена Іванівна; Сухаренко, Елена Ивановна; Sukharenko, Olena; Ганчук, Максим Миколайович; Ганчук, Максим Николаевич; Hanchuk, Maksym; Ангеловська, Алла Олександрівна; Ангеловская, Алла Александровна; Anhelovska, Alla (My University, 2018)
UA: З метою забезпечення господарсько-питного та виробничо-технічного водопостачання м. Мелітополь відбір підземних вод виконується в межах Мелітопольської та Ново-Пилипівської ділянок групових водозаборів. EN: In Zaporozhye region, which is characterized by complex natural water supply conditions, namely low water quality in surface sources, their low costs and very uneven distribution across the area, fresh groundwater is critical for water supply of the population of the region with drinking water. In order to provide economic, drinking and industrial water supply in the city of Melitopol, the selection of groundwater is carried out within the Melitopol and Novo -Pylypivsky sections of group water intakes.
Hydrogeological conditions of Melitopol district of Melitopol city waterintake
Keywords: hydrogeological conditions; aquifer; aquifers; granulometric composition of rocks; coefficient of filtration; water intake; водозабір; питна вода; водопостачання; підземні води; гідрогеологічні умови; водоносний горизонт; водоносні породи; гранулометричний склад порід; коефіцієнт фільтрації